Entangled territorialities : negotiating Indigenous lands in Australia and Canada - Poirier, Sylvie, 1953-; Dussart, Françoise (University of Toronto Press, 2017)
Entangled Territorialities offers vivid ethnographic examples of how Indigenous lands in Australia and Canada are tangled with governments, industries, and mainstream society.